Potential functions of histone H3.3 lysine 56 acetylation in mammals - Lei Fang; Danqi Chen; Jingzi Zhang; Hongjie Li; Beatrix Bradford; Chunyuan Jin (Epigenetics, 2022)
H3K56 acetylation (H3K56Ac) was first identified in yeast and has recently been reported to play important roles in maintaining genomic stability, chromatin assembly, DNA replication, cell cycle progression and DNA repair. Although H3.1K56Ac has been relatively well studied, the function of H3.3K56Ac remains mostly unknown in mammals. In this study, we used H3.3K56Q and H3.3K56R mutants to study the possible function of H3.3K56 acetylation. The K-to-Q substitution mimics a constitutively acetylated lysine, while the K-to-R replacement mimics a constitutively unmodified lysine. We report that cell lines harbouring mutation of H3.3K56R exhibit increased cell death and dramatic morphology changes. Using a Tet-Off inducible system, we found an increased population of polyploid/aneuploid cells and decreased cell viability in H3.3K56R mutant cells. Consistent with these results, the H3.3K56R mutant had compromised H3.3 incorporation into several pericentric and centric heterochromatin regions we tested. Moreover, mass spectrometry analysis coupled with label-free quantification revealed that biological processes regulated by the H3.3-associating proteins, whose interaction with H3.3 was markedly increased by H3.3K56Q mutation but decreased by H3.3K56R mutation, include sister chromatid cohesion, mitotic nuclear division, and mitotic nuclear envelope disassembly. These results suggest that H3.3K56 acetylation is crucial for chromosome segregation and cell division in mammals.